Building R&D leadership and credibility - Uttal, Bro
Bro Uttal, Alan Kantrow, Lawrence H. Linden, and B. Susan Stock suggest how to close the gap between the leadership a company needs and the leadership it often gets from its technical heads.
The opinions of a broad cross section of chief technical officers and their CEOs provide tools any CTO can use to build his or her own credibility.
Despite a consensus that R&D prowess is key to competitiveness, senior R&D managers often feel disenfranchised, cut off from opportunities to help their corporations manage technology for maximum advantage. IRI-sponsored interviews at 24 major corporations indicate that gaps often may exist between the type of R&D leadership a company needs and the type it gets, and that R&D managers can close these gaps themselves by working to build their credibility with top managers. As exemplified by outstanding R&D leaders, best practices for building credibility include acting like a "technical businessman," making R&D accountable to the corporation, and involving general managers in R&D decisions. The authors describe these practices in detail and offer guidelines for measuring leadership gaps and moving to close them.